ANALYSIS OF KEY INDICATORS OF LABOR RESOURCES IN SURKHANDARYA REGION (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the composition of labor resources in the Surxondaryo region, their number, employment level, and the distribution of the economically active population by sectors. The study examines demographic growth in the region, the age structure and gender ratio of the working-age population, as well as the proportion of employed and unemployed people based on statistical data. Proposals and recommendations have been developed to improve the qualitative indicators of labor resources, enhance the level of professional training, and create modern job opportunities.